1992
DOI: 10.1111/j.1346-8138.1992.tb03725.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Effects of Fluorescein on β‐Lactam Rash II: Enhancing Effects of Fluorescein on Generalized Rash Induced by β‐Lactam Antibiotics in Guinea Pigs

Abstract: Healthy volunteers, who were receiving intravenous injections of cefclidin (CFCL) with frequent concomitant use of fluorescein (F) and oxybuprocain (O) in the eyes for measurement of ocular tension, developed drug eruptions at the high frequency of 66.7%. The injection of CFCL alone induced the eruptions at an incidence of 2.8%. The cause of this high eruption rate was thought to be the simultaneous treatment with F and/or O. Therefore, we conducted experiments with CFCL-induced generalized rash (GR) in guinea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…2 cases of immediate‐type hypersensitivity reactions have previously been reported (8, 9). To our knowledge, except in the guinea pig (10), no delayed‐type hypersensitivity reaction has previously been described. In patient no.…”
Section: Discussionmentioning
confidence: 93%
“…2 cases of immediate‐type hypersensitivity reactions have previously been reported (8, 9). To our knowledge, except in the guinea pig (10), no delayed‐type hypersensitivity reaction has previously been described. In patient no.…”
Section: Discussionmentioning
confidence: 93%
“…We have observed that fluorescein enhanced the incidence and the intensity of generalized rashes induced by 13-lactam antibiotics in guinea pigs. These data will be presented and discussed in the following paper (8).…”
Section: Resultsmentioning
confidence: 99%
“…Since the skin lesion developed when nicergorine was administered along with the six other kinds of drugs, drug interactions might have played a role in the devleopment of the eruption. For instance, the enhancing effects of fluorescein on generalized rashes induced by ,B-Iactam antibiotics were reported in an animal model (6).…”
Section: Discussionmentioning
confidence: 99%